2004
DOI: 10.1158/1078-0432.ccr-03-0476
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a T-Helper Peptide from Carcinoembryonic Antigen

Abstract: Purpose: The purpose of this research was to identify promiscuous T-helper cell determinants (THd) from carcinoembryonic antigen (CEA) to be used to prime T-cell help for cancer therapy. CEA was selected because this antigen is expressed in an important variety of carcinomas.Experimental Design: Potential promiscuous THd from CEA were predicted using available computer algorithms. Predicted peptides were synthesized and tested in binding experiments to different HLA-DR molecules. Binder peptides were then used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Th2 immunity) to CEA relative to normal healthy controls [40]. In our study, some important CEA HLA-DR epitopes reported in previous studies [41] may have been overlooked because the basis of our discovery process was elevated IFNγ (i.e. Th1) immunity.…”
Section: Discussionmentioning
confidence: 71%
“…Th2 immunity) to CEA relative to normal healthy controls [40]. In our study, some important CEA HLA-DR epitopes reported in previous studies [41] may have been overlooked because the basis of our discovery process was elevated IFNγ (i.e. Th1) immunity.…”
Section: Discussionmentioning
confidence: 71%
“…The first possibility is most likely for CEA because the Th cells identified were reactive with the purified antigen, and predictions using a web-based algorithm 3 indicate that many of the CEA peptides that stimulate Th cell responses show high affinity for common MHC class II molecules. Previous studies (27,28,30,31) of Th cells reactive with epitopes on CEA did not address ignorance as a mechanism of tolerance because they did not determine whether the responsive population had previously been activated in vivo. Here, we characterize CEA-specific Th cells that mediate proliferation with primary kinetics and express the CD45RA isoform that is characteristic of naive or quiescent Th cells (33,34) and which have therefore remained ignorant in vivo despite the presence of antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several techniques have been developed to help stimulate a stronger and more durable immune response. These include the use of multiple peptides in a single vaccine, and the addition of immune stimulatory adjuvants such as helper peptides, molecules to help induce the MHC‐I CD4 T‐cell (TH2)–mediated response,85 and cytokines to help break tolerance 86. Although these peptide vaccines plus adjuvant cocktails have been found to often elicit strong cytotoxic T‐cell responses measured by tetramers and ELISPOT, rarely has tumor regression coincided with this response 82.…”
Section: Melanoma Vaccinesmentioning
confidence: 99%